Increased factor VIII plays a significant role in plasma hypercoagulability phenotype of patients with cirrhosis. (17th May 2018) - Sinegre, T.; Duron, C.; Lecompte, T.; Pereira, B.; Massoulier, S.; Lamblin, G.; Abergel, A.; Lebreton, A.
Summary: Essentials The role of increased factor VIII in cirrhosis‐induced hypercoagulability has never been demonstrated. Factor VIII and protein C effects were characterized by thrombin generation with thrombomodulin. Factor VIII elevation plays a significant role in cirrhosis‐induced plasma hypercoagulability. Only protein C and factor VIII normalization led to thrombin generation similar to controls. Summary: Background: In cirrhosis, thrombin generation (TG) studied in the presence of thrombomodulin (TM) indicates plasma hypercoagulability. Although the role of protein C (PC) deficiency has been investigated, the influence of an increase in the factor VIII level has never been addressed. Objectives: We investigated the roles of high FVIII and low PC levels in increased TG in the presence of TM. Methods: Blood samples were prospectively collected from 35 healthy controls and 93 patients with cirrhosis (Child–Turcotte–Pugh [CTP]‐A, n  = 61; CTP‐B, n  = 19; and CTP‐C, n  = 13) and FVIII levels > 150% ( n  = 48) and/or PC levels < 70% ( n  = 88). TG was performed with tissue factor (5 pm ), phospholipids, and TM (4 nm ). FVIII and PC levels were normalized by adding an inhibitory anti‐FVIII antibody and exogenous PC, respectively. Results: The endogenous thrombin potential (ETP) in the presence of TM was higher in patients than in controls. After FVIII normalization, the ETP (median) decreased from 929 nm  min to 621 nm  min (CTP‐A), 1122 nm  min to 1082 nm  min (CTP‐B), and 1221 nm  min to 1143 nm  min (CTP‐C); after PC normalization, it decreased from 776 nm  min to 566 nm  min (CTP‐A), 1120 nm  min to 790 nm  min (CTP‐B), and 995 nm  min to 790 nm  min (CTP‐C). The ETP was reduced by 17% and 30%, respectively, but normal TG was not restored. When both FVIII and PC levels were normalized, the ETP decreased from 929 nm  min to 340 nm  min (CTP‐A), 1122 nm  min to 506 nm  min (CTP‐B), and 1226 nm  min to 586 nm  min (CTP‐C), becoming similar to control levels. Conclusion: Cirrhosis‐induced plasma hypercoagulability, as demonstrated in these experimental conditions, can be partly explained by opposite changes in two factors: PC level (decrease) and FVIII level (increase).